Modulation of structural and photoluminescence properties of ZnO thin films for photodetector and resistive switching applications - Kossar, Shahnaz; Rasool, Asif; Rafiudeen, Amiruddin; Ahmad Syakirin, Ismail @ Rosdi; M H, Mamat; Sharma, Jyoti (Institute of Physics, 2025)
The recent research work focuses on the realization of ITO/ZnO/Ag-based multifunctional devices. The fabricated devices exhibits multi-task operations, including ultraviolet (UV) light detection and non-volatile resistive switching (RS) memory applications. The intermediate ZnO switching layers were deposited using the spin-coating technique at 2500 rpm. The structural analysis validates the presence of wurtzite structure along the c-axis. The morphological analysis reveals that the grains are uniformly distributed of the deposited thin films. The PL emission spectrum of the ZnO thin film shows highly intensive peak at 382 nm. The obtained ZnO thin film was formed onto ITO substrate which was sandwiched between top and bottom Ag electrodes. The current–voltage measurements (I–V) and ln I–V plots characteristics of the fabricated ITO/ZnO/Ag devices were examined for UV photoresponse (under dark and UV illumination), and resistive switching (RS) behavior. The fabricated device shows a stable resistive switching characteristics and UV photoresponse with photoresponsivity (R) value of 0.52 mA W−1. The fabricated ITO/ZnO/Ag devices shows rise time 4.35 s and 9.25 s decay time respectively. The optical sensing mechanism of ITO/ZnO/Ag were explored by oxygen (O2) adsorption/desorption processes in Ag/ZnO and ITO/ZnO junctions across the interface.